A PROSPECTIVE OBSERVATIONAL STUDY OF MONITORING AND REPORTING OF ANTIMICROBIAL DRUGS ASSOCIATED ADVERSE DRUG REACTIONS AND THEIR SIGNIFICANCE ON PATIENTS SAFETY AND HEALTH-CARE OUTCOMES - ZEENATH UNNISSA; MAHER UNISSA; SHAISTA KHAN; NAZIYA THASLEEM; NIKHATH FATIMA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Adverse drug reaction (ADR) surveillance and reporting practices are at an early stage of development within the Indian context. The pharmacovigilance rate in India falls below 1%, which is notably lower compared to the global average of 5%. India holds the position of being the fourth most significant contributor to the pharmaceutical industry worldwide. Therefore, there exists a pressing demand to enhance the pharmacovigilance framework for safeguarding the health of the Indian population. ADR is defined as the unintended, obnoxious, and unwanted reaction due to the use of a drug. The administration of antimicrobial agents causes various ADR that has been analyzed throughout the study. The main objective of the research is to monitor and report the adverse drug reaction caused by antimicrobial drugs Methods: A prospective observational study was carried out in the various departments of the hospital with duration of 3 months including 100 patients using patient profile form and ADR reporting forms and analyzing with the scales for causality, severity, and preventability assessment. Results: During the study, 29 ADRs were found among 100 patients, with an incidence rate of 9.6%, more common in females (52%) than in males (48%). ADRs were most frequently reported in the age group of 35–51 years (34%), then 18–34 years (28%), and 1–17 years (24%). The general medicine department reported the highest number of ADRs (66%), followed by the pediatric department (24%). Cephalosporins caused the most ADRs (35%). Common ADRs included constipation, diarrhea (34%) and rashes, nausea, and vomiting (34%). Naranjo scale indicated that the causality of ADRs was probable (52%). Hartwig severity scale showed 55% ADRS to be mild. Schumock and Thornton method found that 76% of ADRs were preventable.Management of most of ADRs included drug withdrawal (52%). Conclusion: The majority of cephalosporin-related side effects, which included constipation, diarrhoea, and rashes, were observed. Most of the patients got better with the help of ADR monitoring and management. Finding and treating drug-related problems early make patients feel better and keep them safe. This study shows health-care system why it is important to monitor and report ADR caused by drugs.